Photonic crystal fiber Bragg grating based sensors - Opportunities for applications in healthcare - Sugden, Kate; Berghmans, Francis; Geernaert, Thomas; Sulejmani, Sanne; Thienpont, Hugo; Van Steenberge, Geert; Van Hoe, Bram; Dubruel, Peter; Urbanczyk, Waclaw; Mergo, Pawel; Webb, David J.; Kalli, Kyriacos; et al. (My University, 2011)
We review the state-of-the-art in photonic crystal fiber (PCF) and microstructured polymer optical fiber (mPOF) based mechanical sensing. We first introduce how the unique properties of PCF can benefit Bragg grating based temperature insensitive pressure and transverse load sensing. Then we describe how the latest developments in mPOF Bragg grating technology can enhance optical fiber pressure sensing. Finally we explain how the integration of specialty fiber sensor technology with bio-compatible polymer based micro-technology provides great opportunities for fiber sensors in the field of healthcare.
Keywords: Biocompatible; Biomechanical; Embedded; Fiber bragg; Micro-structured optical fibers; Microtechnology; Optical fiber sensor; Biomechanics; Crystal whiskers; Fiber Bragg gratings; Fiber optic sensors; Fibers; Health care; Nonlinear optics; Photonic crystals; Photonics; Polymers; Sensors; Technology; Photonic crystal fibers